Defect-Induced Properties and Thermodynamics of La0.5Ba0.5CoO3–δ. Issue 2 (1st February 2022) - Malyshkin, Dmitry A.; Sereda, Vladimir V.; Sednev-Lugovets, Anton L.; Ivanov, Ivan L.; Tsvetkov, Dmitry S.; Zuev, Andrey Yu.
Abstract : The defect structure model of La0.5 Ba0.5 CoO3– δ was successfully verified using a combined set of coulometric and thermogravimetric data. The results were used to model the dependences of Seebeck coefficient, measured vs T and p O2 simultaneously with the total conductivity, and chemical strain of this oxide. The partial molar enthalpy of oxygen in La0.5 Ba0.5 CoO3– δ was calculated from the defect structure model and used to evaluate the enthalpy increments and high-temperature heat capacity of an oxide with constant chemical composition, La0.5 Ba0.5 CoO2.99, from the drop calorimetric measurement results in air. The standard enthalpies of formation of cubic La0.5 Ba0.5 CoO2.95 and double LaBaCo2 O5.90 perovskites, and the enthalpy of cation ordering in A-sublattice of La0.5 Ba0.5 CoO2.95, were found using the results of solution calorimetry at 298.15 K. With the data obtained, we predicted the chemical compatibility of La0.5 Ba0.5 CoO3– δ with solid oxide fuel cell (SOFC) electrolyte materials.